The Correlation between the Levels of Family’s Knowledge about Pulmonary Tuberculosis and Efforts in Prevention of Pulmonary Tuberculosis Infection - Sukartini, Tintin; Hanif, Dady Zharfan; Hidayati, Laily (International Journal of Psychosocial Rehabilitation, 2020)
Abstract— Pulmonary tuberculosis (TB) is an infection caused by Mycobacterium tuberculosis. This study aimed to analyze the correlation between family knowledge about pulmonary TB and efforts to prevent the spread of pulmonary TB infection in health centers. This study was a correlational study with a cross-sectional approach. The population in this study were families with pulmonary TB in Primary Healthcare. The sampling method used purposive sampling and obtained 25 samples. The independent variable in this study was family knowledge about pulmonary TB. The dependent variable was the family’s effort to prevent the spread of pulmonary tuberculosis infection. Data were taken using a questionnaire and analyzed by the Spearman rho test with α ≤ 0.05. This study showed that there was a correlation between family knowledge about pulmonary TB and efforts to prevent the spread of pulmonary tuberculosis infection (p = 0,000, r = 0.695). Higher knowledge can increase family efforts to prevent the spread of pulmonary tuberculosis infections. The results of this study were expected to increase the motivation of nurses to provide health education and counselling to people who still do not understand how to prevent the transmission of pulmonary TB infection.